The Missing Productive Vocational High School Teacher Competency Standard in the Indonesian Education System - Estriyanto, Yuyun; Kersten, Steffen; Pardjono, Pardjono; Sofyan, & Herminarto (Journal of Technical Education and Training, 2017)
Teaching profession reform in the Indonesian education system began with the enactment of National Law on Teachers and Lecturers. An exception to the productive vocational high school teacher competency standard in the government regulation is identified to be a problem in the vocational teacher professionalism development system. This article reviews in what way it is missing and what the effects are. Comprehensive analysis on the vocational high school teaching context indicates the importance of occupational-specific competency standard for vocational teachers. This article reviews how the missing standard affects the vocational teacher professionalism development programs in the national education system.